Adjuvant treatment with ursodeoxycholic acid may reduce the incidence of acute cardiac allograft rejection - Bährle-Szabó, Susanne; Szabó, Gábor; Stiehl, Adolf; Theilmann, Lorenz; Dengler, Thomas; Zimmermann, Rainer Johannes; Kübler, Wolfgang (The journal of heart and lung transplantation, 1998)
BACKGROUND: The nontoxic bile acid, ursodeoxycholic acid (UDCA), is an effective drug for the treatment of different cholestatic conditions. Furthermore, an immunomodulatory capacity of UDCA has been reported in vitro, as well as in vivo, in different immune-mediated liver diseases and after liver transplantation. - METHODS: In this retrospective study, the influence of UDCA on heart transplant rejection was investigated in 21 cardiac allograft recipients receiving UDCA for cyclosporine-induced cholestasis (500 mg administered twice daily, start of therapy within the first postoperative month, duration >8 weeks). Thirty-one patients not receiving UDCA served as control subjects. All patients received triple-maintenance immunosuppression (cyclosporine, azathioprine, prednisolone). For quantitative comparison of rejection severity, the following score was applied: 0, no specific therapy; 1, temporary increase in oral steroids; 2, intravenous steroids; 3, ATG or OKT3 therapy. - RESULTS: During the first 6 postoperative months, the number of acute rejection episodes requiring specific anti-rejection therapy was significantly lower in the UDCA group as compared with control subjects (1.38 +/- 1.36 vs 2.74 +/- 1.83 rejection episodes per patient, p = 0.005). The cumulative score was significantly lower in the UDCA group as compared with control subjects (2.38 +/- 2.29 vs 5.06 +/- 3.61, p = 0.004). - CONCLUSIONS: These initial data indicate a beneficial effect of adjuvant UDCA treatment in the early phase after heart transplantation probably related to immunomodulating properties of UDCA, which may be used therapeutically after organ transplantation.